PENGARUH PEMBELAJARAN QUANTUM BERBANTUAN PERMAINAN DALAM PEMBELAJARAN TERHADAP KEAKTIFAN DAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS V - Samadhi, Ni Nyoman Nitha; Riastini, Putu Nanci (International Journal of Elementary Education, 2017)
This research aims is to determine the differences of activity and learning outcomes of science between groups of students who were taught by learning Quantum assisted games and groups of students who were taught not with learning Quantum assisted game to elementary school students in V grade  at Gugus II Santalia,  Kubutambahan district, in academic year 2016/2017. This type of research is quasi experiment, with non equivalent design post test only control group design. The population in this study is the entire class V of elementary school in gugus II Santalia. The research sample in class V elementary school number 1 Kubutambahan as experimental group and class V elementary school number 7 Kubutambahan as control group obtained by random sampling technique by way of class lottery. Analytical  methods that used in this study consist of  descriptive analysis and inferential analysis using the t-test (polled variance). The results showed that there was a difference of activity and learning outcomes between the experimental group and the control group. The findings are that students become more active, enthusiastic, and happy during the learning process. In addition the steps of learning Quantum help students more easily understand the material. Thus the learning of Quantum-assisted games has an effect on the activity and learning outcomes of science students of grade V in Gugus II Santalia Kubutambahan distric of academic year 2016/2017